2010
DOI: 10.2105/ajph.2008.155432
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Depression Following Combat Deployment in Support of the Wars in Iraq and Afghanistan

Abstract: Objective. We investigated relations between deployment and new-onset depression among US service members recently deployed to the wars in Iraq and Afghanistan. Methods. We included 40 219 Millennium Cohort Study participants who completed baseline and follow-up questionnaires and met inclusion criteria. Participants were identified with depression if they met the Primary Care Evaluation of Mental Disorders Patient Health Questionnaire criteria for depression at follow-up, but not at baseline. Results. Deplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
159
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(179 citation statements)
references
References 79 publications
18
159
0
Order By: Relevance
“…It was not surprising that our overall rates of depression and substance use disorder because of alcohol were lower than those reported in MCS, because MCS identified conditions through surveys, whereas we identified conditions through TRICARE health records. The overall rate of new onset of depression in MCS was 4% (Wells et al 14 ; Tables 2 and 3), whereas our overall rate of major depression was 2% (see the online appendixes, available at http://www.ajph. org).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It was not surprising that our overall rates of depression and substance use disorder because of alcohol were lower than those reported in MCS, because MCS identified conditions through surveys, whereas we identified conditions through TRICARE health records. The overall rate of new onset of depression in MCS was 4% (Wells et al 14 ; Tables 2 and 3), whereas our overall rate of major depression was 2% (see the online appendixes, available at http://www.ajph. org).…”
Section: Discussionmentioning
confidence: 74%
“…The MCS found that men and women deployed with combat exposure had, respectively, 1.32 and 2. 13 times the odds of having depression compared with those not deployed 14 and found weak evidence of any impact of a combat deployment on drinking outcomes among active duty respondents. 15 Besides the MCS, 1 study, using a 2008 Department of Defense Health Related Behaviors Survey, found that service members with any combat deployment had significantly higher rates of heavy alcohol and cigarette use.…”
mentioning
confidence: 87%
“…The most common identification strategy used in the medical literature (see, for example, Wells et al, 2010;Smith et al, 2009;Jacobson et al, 2008) has been to compare those deployed to combat with non-deployed active duty and reservist soldiers. However, non-deployment may not be exogenous, as selection into the Reserves or National Guard-which comprise a relatively larger share of non-deployed armed services personnel than active duty soldiers-may be nonrandom (Hirsch and Mahey, 2003) and active-duty soldiers who remain non-deployed for long periods of time may be non-deployable for reasons related to physical or mental health (Department of the Army AR 614-30, 2010;Cesur et al, 2011).…”
Section: Identificationmentioning
confidence: 99%
“…Data from Canada's closest allies [1][2][3][4][5][6][7] have shown that an important minority of their personnel deployed to the conflicts in Southwest Asia have mental health problems, many apparently related to their deployment. Mental disorders have important implications for military and veteran organizations and are leading causes of impaired productivity, 8 absenteeism 8 and turnover.…”
mentioning
confidence: 99%